Volatility Dynamics of the Inflation Expectation - Erdogan, Mefule Findikci; Karagoz, Hueseyin; Alp, Selcuk; Alp, Elcin Aykac (ISTANBUL UNIV, 2025)
This study investigates how the Central Bank of the Republic of Turkey fulfilled its responsibility of ensuring price stability by focusing on inflation and inflation expectations volatility between August 2001 and November2023.The study utilised ARCH models, preferred in financial series, to demonstrate time-varying volatility and volatility clustering to examine the alterations in the volatility of inflation and inflation expectations. Achieving price stability, these are considered as indicators. The threshold model analysed inflation behaviour around a specific threshold by presidential terms and presented different coefficients and standard errors. Raising concerns about recent policy changes weakening the institutional and operational independence of the CBRT, the analysis is structured around the CBRT governors' tenures. The findings show Serdenge & ccedil;ti's tenure as the most successful, with inflation in single digits. Y & imath;lmaz and Ba & scedil;& ccedil;& imath; also maintained stability despite the crises. During the & Ccedil;etinkaya term, the independence of the CBRT was questioned, inflation rates climbed, and tensions with policymakers increased. Uysal pursued a low-interest rate policy and kept inflation high but stable. A & gbreve;bal raised interest rates but was dismissed early. Kavc & imath;o & gbreve;lu's tenure saw record inflation and volatility. In June 2023, Erkan's appointment promised a return to orthodox policies, but their effectiveness in controlling inflation and managing expectations remains uncertain.
Keywords: Inflation; expectation; ARCH; Threshold; Business & Economics